Physiochemical, Insecticidal, and Antidiabetic Activities of Senna occidentalis Linn Root - Tahani Osman Issa; Ahmed Ibrahim Mohamed Ahmed; Yahya Sulieman Mohamed; Sakina Yagi; Abdelrafie Mohamed Makhawi; Tarig Osman Khider (Biochemistry Research International)
The present study aimed to investigate the physiochemical activities of Senna occidentalis (Linn) roots and phytochemicals as insecticidal (ethyl acetate and methanol) and antidiabetic (ethanolic extract) activities. Physicochemical properties were carried out by using Association of Official Analytical Chemist methods; thin layer chromatography was carried out according to the Stahl method. Larvicidal activity and LD50 were studied against the third instar of Culex quinquefasciatus mosquito larvae to detect and extract toxicity. The ethanolic extracts of the roots were orally tested at the dose 200 mg/kg for the hypoglycemic effect on induced hyperglycemia in normal rats, assessed in the ethanol extract, and were compared with diabetic control and standards glibenclamide 10 mg/kg. Physiochemical parameters showed high rate in the nitrogen-free extract (69.6%), curd fiber (14.5%), crude proteins (8.15%), ether extract (3.75%), and both ash and moisture (2%), and high concentrations values were found in potassium (43 mg/l) followed by phosphorous (28.5 mg/l), calcium (15 mg/l), sodium (3.65 mg/l), and magnesium (0.145 mg/l). In this part, phytochemical compounds showed high amount of alkaloids, triterpene, flavonoids, tannins, sugars, and few amount of anthraquinone glycosides. Thin-layer chromatography (TLC) studies different colored phytochemical constituted with different Rf values. All the spots are colored under UV light, but some are localized colorless after spaying. The ethyl acetate (EtAc) extract showed eight spots, and the methanol (MeOH) extract showed thirteen spots. The larvicidal activity showed that the ethyl acetate extract was safe against mosquito larvae with an LD50 value 1412.54 (p<0.05), and the methanol extract had moderate larvicidal activity against mosquito larvae with an LD50 value 257.54 (p<0.05), while the ethanolic extract of Senna occidentalis (L.) causes a favorable hypoglycemic activity when compared to control significant reduction by [53.15%, 32.87%, and 20.94%], respectively, as well as standard glibenclamide. Based on the various data of the physicochemical parameters, TLC spots, and phytochemical compounds of Senna occidentalis root, they could be used as references standards for manufacturing units of Senna occidentalis root larvicidal and antidiabetic drugs.